# solve the equation `(x-a)/(x+a) = (x+a)/(2x-a)` for x, when a is a constant.

*print*Print*list*Cite

(x-a)(2x-a)=(x+a)(x+a)

2x^2-ax-2ax+a^2=x^2+ax+ax+a^2

2x^2-x^2-ax-2ax-ax-ax+a^2-a^2=0

x^2-5ax=0

x-5a=0

x=5a; x=0

Cross Multiply

- `(x-a)(2x-a)=(x+a)^2`

FOIL Both sides (First, Outside, Inside, Last)

- `2x^(2)-xa-2xa+a^(2)=x^(2)+xa+xa+a^(2)`

Simplify

- `2x^(2)-3xa+a^(2)=x^(2)+2xa+a^(2)`

Bring all terms to one side and simplify

- `x^(2)-5xa=0`

Q: What do the 2 terms have in common?

A: `x`

`x(x-5a)=0`

`x=0, 5a`

Because the 2 terms have x in common, we can factor out the x on both sides then simplify.

`(x-a)/(x+a) = (x+a)/(2x-a)` the firs step is to cross multiply

`2x^2 - 3xa + a^2 = x^2 + 2xa +a^2` expand the answers

`2x^2 - 3xa + a^2 - x^2 - 2xa - a^2` = 0 transpose all the factors to one side

`x^2 - 5xa = 0` add or subtract all possible factors and equate with 0

`x (x - 5a) = 0` get the common factor

`x = 0 x=5a` get the value of x

The final answer should be x = 0 and x = 5a

###### ` `

` `

cross multiply:

(x-a)(2x-a) = (x+a)(x+a)

foil

2x^2 - ax - 2ax +a^2 = x^2 +ax +ax+a^2

combine like terms:

2x^2 -3ax + a^2 = x^2 + 2ax + a^2

move them all to one side:

2x^2 -3ax + a^2 - x^2 - 2ax - a^2

combine like terms:

x^2 - 5ax

factor our

x(x-5a)

set them equal to 0

*x=0*

x-5a=0

**x= 5a**

cross multiply:

(x-a)(2x-a)=(x+a)(x+a)

2x^2-ax-2ax+a^2=x^2+ax+ax+a^2

bring all variables to the left side of the equation and equate to zero (transpose)

2x^2-x^2-ax-2ax-ax-ax+a^2-a^2=0

x^2-5ax=0

x-5a=0

x=5a; x=0

`(x-a)/(x+a)` = `(x+a)/(2x-a)` Your first step is to cross multiply, which is taking the denominator and multiplying it to the equation that is on the opposite of the equal sign.

`(x-a)(2x-a)` = `(x+a)(x+a)` This is what it looks like after cross-multiplying.

The next step is to FOIL (first, outer, inner, last) the equation. Remember the signs of the equations and what happens when you multiply two negatives!

`2x^2 - ax -2xa +a^2` = `x^2 + 2ax + a^2` You can see that this is not in the simplest form. To make this easier, combine like terms such as the `ax` .

`2x^2 - 3ax + a^2` = You should also notice that both sides of the equation has `a^2` . When something is on both sides of the equation, you can simply ignore it.

`2x^2 - 3ax` = `x^2 + 2ax` Set the entire equation to zero by moving one side to the other. I prefer keeping the largest polynomial a positive number.

`x^2 - 5ax` = `0` You can factor out the `x` and set equal to zero.

`(x)(x-5a)` = `0`

`x = 0` and `x-5a = 0` Finally, solve for `x` .

Your answer should be: `x=0` and `x=5a` .` <br> `

`(x-a)(2x-a)=(x+a)^2` (Cross multiply)

`2x^2-ax-2ax+a^2=x^2+2ax+a^2` (Expand both sides)

`2x^2-3ax+a^2=x^2+2ax+a^2` (Simplify equation)

`x^2-5ax=0` (Simplify equation)

`x(x-5a)=0` (Factor out the x from left-hand side)

From the equation above, we see that either:

`x=0 or x-5a=0`

When `x-5a=0`, we get that `x=5a`

So the final answer is `x=0 or x=5a`